Strongly lensed cluster substructures are not in tension with ΛCDM. Issue 1 (17th May 2021) - Bahé, Yannick M
ABSTRACT: Strong gravitational lensing observations can test structure formation models by constraining the masses and concentrations of subhaloes in massive galaxy clusters. Recent work has concluded that cluster subhaloes are more abundant and/or concentrated than predicted by Λ cold dark matter (ΛCDM) simulations; this finding has been interpreted as arising from unidentified issues with simulations or an incorrect understanding of the nature of dark matter. We test these hypotheses by comparing observed subhalo masses and maximum circular velocities v max to predictions from the high-resolution Hydrangea galaxy cluster simulation suite, which is based on the successful EAGLE galaxy formation model. Above ${\sim}10^{11}\, M_\odot$, the simulated subhalo mass distribution and mass– v max relation agrees well with observations, due to the presence of baryons during tidal stripping. Similar agreement is found for the lower resolution IllustrisTNG300 simulation. In combination, our results suggest that the abundance and concentration of cluster substructures are not in tension with ΛCDM, but may provide useful constraints for the refinement of baryon physics models in simulations.